(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Adaptive façades, developed in recent years to increase user comfort and reduce energy consumption, offer innovative solutions for optimizing daylight regulation in interior spaces. This study examines adaptive façade systems in the context of daylight performance. The study adopts a systematic methodological approach that combines qualitative and bibliometric analyses of existing literature. The proposed framework synthesizes existing façade classification proposals, integrating categories such as movement typologies, control strategies, and daylight-specific performance metrics to provide a coherent classification approach. Subsequently, an extensive review of existing studies in the field was conducted, key concepts and dominant trends were identified, and the scope of the study was narrowed. A selected group of studies from the existing literature was then subjected to detailed evaluation and analyzed using the new classification system. The aim of this study is to map adaptive façades for daylighting using a bibliometric and systematic approach, propose a new theoretical framework based on previous classifications, and apply this framework to selected studies to identify trends, research gaps, and future directions.